Microparticle Analysis in Disorders of Hemostasis and Thrombosis - Mooberry, Micah J. (Cytometry A, 2015)
Microparticles (MPs) are submicron vesicles released from the plasma membrane of eukaryotic cells in response to activation or apoptosis. MPs are known to be involved in numerous biologic processes, including inflammation, the immune response, cancer metastasis, and angiogenesis. Their earliest recognized and most widely accepted role, however, is the ability to promote and support the process of blood coagulation. Consequently, there is ongoing interest in studying MPs in disorders of hemostasis and thrombosis. Both phosphatidylserine (PS) exposure and the presence of tissue factor (TF) in the MP membrane may account for their procoagulant properties, and elevated numbers of MPs in plasma have been reported in numerous prothrombotic conditions. To date, however, there are few data on true causality linking MPs to the genesis of thrombosis. A variety of methodologies have been employed to characterize and quantify MPs, although detection is challenging due to their submicron size. Flow cytometry (FCM) remains the most frequently utilized strategy for MP detection; however, it is associated with significant technological limitations. Additionally, pre-analytical and analytical variables can influence the detection of MPs by FCM, rendering data interpretation difficult. Lack of methodologic standardization in MP analysis by FCM confounds the issue further, although efforts are currently underway to address this limitation. Moving forward, it will be important to address these technical challenges as a scientific community if we are to better understand the role that MPs play in disorders of hemostasis and thrombosis.